Effect of targeted temperature management on neurological and survival outcomes in patients undergoing extracorporeal cardiopulmonary resuscitation - Chi Chan Lee; Yu-Yu Tu; Ping-Yi Lin; You-Cian Lin (PLoS ONE, 2026)
Objectives Targeted temperature management (TTM) has been a fundamental component of post-resuscitation care for patients experiencing cardiac arrest for many years. This study aims to investigate the association between TTM and clinical outcomes in patients undergoing extracorporeal cardiopulmonary resuscitation (ECPR). Methods This retrospective cohort study was conducted at a single tertiary medical center in Taiwan. A total of 360 patients were screened between January 2015 and May 2023, with 148 excluded. After selection, 212 patients were included in the final analysis, with 79 receiving TTM and 133 not receiving TTM. Findings Patients in the TTM group had a higher rate of successful weaning from extracorporeal membrane oxygenation (64.6% vs. 42.1%, p = 0.002), survival to discharge (58.2% vs. 38.3%, p = 0.005) and lower cerebral performance category (CPC) scores at discharge (3.6 vs. 4.2, p = 0.001). A higher proportion of patients in the TTM group had a CPC score of 1–2 points at discharge, indicative of a favorable neurologic outcome (29.1% vs. 10.5%, p < 0.001). After adjusting for potential confounders, TTM was significantly associated with reduced odds of in-hospital death (adjusted odds ratio [OR] 0.34, 95% confidence interval [CI] 0.15–0.72, p = 0.006) and poor neurological outcomes (CPC 3–5; adjusted OR 0.30, 95% CI 0.12–0.72, p = 0.008). Conclusions Among patients receiving ECPR, the use of TTM is associated with improved neurological outcomes and increased survival to hospital discharge. Future randomized controlled trials are needed to elucidate the pathophysiology and clinical impact of combining TTM with ECPR.